Pedagogical Conditions for the Development of Altruistic Virtues in Students Through the Subject "Education" - Olmasovich, Yuvashov Sherzod (International Journal on Orange Technologies, 2021)
In the article, the interest in the axiological approach in the pedagogical conditions of the development of altruistic qualities in students through the subject of "education" is associated with changes in the socio-cultural environment, the emergence of a new global moral crisis. Therefore, in the new millennium, the scientific community is actively working to identify, regulate and systematize the values that must be mastered by humanity.